The effects of a leaflet‐based intervention, 'Hypos can strike twice', on recurrent hypoglycaemic attendances by ambulance services: A non‐randomised stepped wedge study. Issue 10 (12th June 2021) - Botan, Vanessa; Law, Graham R.; Laparidou, Despina; Rowan, Elise; Smith, Murray D.; Ridyard, Colin; Brewster, Amanda; Spaight, Robert; Spurr, Keith; Mountain, Pauline; Dunmore, Sally; James, June; et al.
Abstract: Aims: We aimed to investigate the effect of an intervention in which ambulance personnel provided advice supported by a booklet—'Hypos can strike twice'—issued following a hypoglycaemic event to prevent future ambulance attendances. Methods: We used a non‐randomised stepped wedge‐controlled design. The intervention was introduced at different times (steps) in different areas (clusters) of operation within East Midlands Ambulance Service NHS Trust (EMAS). During the first step (T0), no clusters were exposed to the intervention, and during the last step (T3), all clusters were exposed. Data were analysed using a general linear mixed model (GLMM) and an interrupted‐time series analysis (ITSA). Results: The study included 4825 patients (mean age 65.42 years, SD 19.42; 2, 166 females) experiencing hypoglycaemic events attended by EMAS. GLMM indicated a reduction in the number of unsuccessful attendances (i.e., attendance followed by a repeat attendance) in the final step of the intervention when compared to the first (odds ratio OR: 0.50, 95%CI: 0.33–0.76, p  = 0.001). ITSA indicated a significant decrease in repeat ambulance attendances for hypoglycaemia—relative to the pre‐intervention trend ( p  = 0.008). Furthermore, the hypoglycaemia care bundle was delivered in 66% of attendances during the intervention period, demonstrating a significant level of practice change ( p  < 0.001). Conclusion: The 'Hypos can strike twice' intervention had a positive effect on reducing numbers of repeat attendances for hypoglycaemia and in achieving the care bundle. The study supports the use of information booklets by ambulance clinicians to prevent future attendances for recurrent hypoglycaemic events.